Psychological Service for Ukrainian School Students during the Russian Invasion: Experience of School Psychologists from Kryvyi Rih - Velykodna, Mariana; Deputatov, Vladyslav; Kolisnyk, Lyudmyla; Shestopalova, Olena; Shylo, Oksana (International Journal of Child Health and Nutrition, 2023)
Introduction: After eight years of the war in the East of Ukraine, two years of the COVID-19 pandemic with relevant lockdowns, and two months of bomb alerts, school students and school psychologists from Kryvyi Rih have been dealing with new brutal military actions during the Russian invasion of Ukraine since the 24th February 2022. Purpose: This paper focuses on School Psychological Services’ changes and challenges caused by the Russian invasion. It assesses war-related psychological effects on school students and school psychologists from Kryvyi Rih. Method: Brief non-structured interviews and the survey. Results and Conclusions: After the Russian invasion of Ukraine, School Psychological Services in Kryvyi Rih continued their work remotely, often combining it with in-person meetings (48.5%) and other volunteer activities (27.9%). The surveyed school psychologists (n=48) informed they conducted more individual consultations and psychoeducation and fewer diagnostics than usual to address school students’ changing needs in response to wartime. School psychologists felt more effective and involved with students when they believed they got enough support from colleagues and supervisors, learned crisis interventions, received clear guidance, and did not feel burnout. They appreciated current governmental guidance and felt their post-traumatic growth more when they were safe. After 1.5 months of the war, 43.8% of psychologists experienced burnout. At least a quarter needed additional education, psychological support, easily accessible supervision (especially short and rapid), and guidance for specific cases.